SUN HATS TO PROTECT FROM HARMFUL UV RAYS - АРАБУЛІ , С.І.; АРАБУЛІ , A.Т.; ТРУБА, А.А.; KNUTD, Library (Fashion Industry, 2022)
Purpose. Analysis of design solutions for sun hats and development of a hat that provides maximum protection of the human face from the eff ects of ultraviolet (UV) radiation due to the design and properties of the textile material.. Methodology. Methods of scientifi c analysis and design methods of hats for protection against UV radiation have been used. In conducting experimental research, modern methods have been used to determine the protective properties of textile materials against UV radiation. Results. The state of human disease due to harmful UV radiation according to the World Health Organization (WHO) is given. Skin cancer has been found to occur most often on the head and neck. It is proved that the degree of human exposure can be reduced through the use of protective equipment. The paper focuses on the analysis of the range of sun hats, their effe ctiveness and appropriateness of wearing depending on the season and time of day. The results of scientists' research are presented and a comparative analysis of the eff ectiveness of protection of such sun hats as a wide-brimmed hat, a medium-brimmed hat, a helmet, a bucket hat, a legionnaire's hat and a baseball cap is presented. It was found that the larger the surface of the skin of a person's face covered with a hat, the better it is protected from the eff ects of solar UV radiation. The best protection is provided by a legionnaire's hat.. Scientifi c novelty. Data on the modern range and eff ectiveness of sun protection hats to UV radiation are systematized. It has been experimentally proven that the maximum protection of the human face from the harmful eff ects of UV radiation can be achieved due to the design of the hat and the properties of the textile material. Practical value. The design and technological solution of the legionnaire's hat has been improved, namely, the safety valve has been increased in order to cover the cheeks and fasten it with buttons in the nose area. The legionnaire hat is made of 100% cotton fabric modifi ed with n anoceramic composite (Red S-3B and nanometer I.31PS), which provides "excellent protection" from the negative eff ects of UV radiation.